A retrospective on the state of international advertising research in advertising, communication, and marketing journals: 1963–2014. Issue 3 (3rd May 2016) - Khang, Hyoungkoo; Han, Sangpil; Shin, Sumin; Jung, A-Reum; Kim, Mi-Jeong
Abstract : Scanning from the earliest to the recent literature on international advertising research, this study aimed to provide a more comprehensive and detailed picture of the research trends and patterns across the advertising, marketing, and communication disciplines over the past half century. Findings exhibit continuous growth in terms of the quantity of international advertising studies. While theoretical foundations need to be further solidified and elaborated, methodological and statistical rigors have been increasingly underpinned in international advertising research. Further, this study recognized authorial and institutional productivity, and influential articles in the field of international advertising research. The finding indicates that scholarly endeavors are necessary for diversity of countries studied in future research.